2015
DOI: 10.1089/scd.2015.0100
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Human Primordial Germ Cells into Induced Pluripotent Stem Cells: Efficient Generation of Genetically Engineered Germ Cells

Abstract: Primordial germ cells (PGCs) share many properties with embryonic stem cells (ESCs) and innately express several key pluripotency-controlling factors, including OCT4, NANOG, and LIN28. Therefore, PGCs may provide a simple and efficient model for studying somatic cell reprogramming to induced pluripotent stem cells (iPSCs), especially in determining the regulatory mechanisms that fundamentally define pluripotency. Here, we report a novel model of PGC reprogramming to generate iPSCs via transfection with SOX2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 89 publications
1
20
0
1
Order By: Relevance
“…In human PGCs, the expression of endogenous KLF4 and C-MYC is similar to EGCs, but the expression levels of SOX2 and OCT4 are lower than EGCs. Thus, the reprogramming of PGCs into iPSCs can occur only by employing two transcription factors, SOX2 and OCT4 [55] . Only one study has found that a porcine iPSC line could be established by transfecting six human reprogramming factors (OCT4, SOX2, NANOG, KLF4, LIN28 and C-MYC) which possessed the ability to produce chimeric offspring [42] (Table 1).…”
Section: Derivation Of Pluripotent Stem Cells From Primordial Germ Cellsmentioning
confidence: 99%
“…In human PGCs, the expression of endogenous KLF4 and C-MYC is similar to EGCs, but the expression levels of SOX2 and OCT4 are lower than EGCs. Thus, the reprogramming of PGCs into iPSCs can occur only by employing two transcription factors, SOX2 and OCT4 [55] . Only one study has found that a porcine iPSC line could be established by transfecting six human reprogramming factors (OCT4, SOX2, NANOG, KLF4, LIN28 and C-MYC) which possessed the ability to produce chimeric offspring [42] (Table 1).…”
Section: Derivation Of Pluripotent Stem Cells From Primordial Germ Cellsmentioning
confidence: 99%
“…A panel of OCT4, homeobox transcription factor NANOG (NANOG), Krüppel-like factor 4 (KLF4) and the oncogene avian myelocytomatosis viral oncogene homolog, MYC (C-MYC) might induce reprogramming of testicular germ cells to a stem cell pattern. 32 Correspondingly, malignant germ cells of GCNIS have an especially high expression of OCT4, NANOG, C. elegans homolog of LIN28 (LIN28), SRYbox 17 (SOX17), and KLF4. 33,34 These genetic similarities might be significant for the pathogenesis of TGCT.…”
Section: Finn Edler Von Eyben Et Almentioning
confidence: 99%
“…Transfection with OCT4 and SRY-box 2 (SOX2) might make primordial germ cells undergo reprogramming to an induced pluripotent stem cell pattern, like that of EC. 32 Also in human fibroblasts, transduction of OCT4, SOX2, NANOG, and LIN28 can induce reprogramming to a pluripotent stem cell pattern. 35 Also, a combination of the transcription factors OCT4, NANOG, and KFL4 and the oncogene MYC might induce the stem cell pattern.…”
Section: Finn Edler Von Eyben Et Almentioning
confidence: 99%
“…In addition to this, protein homoeostasis in somatic cells is well-maintained when germ cells are damaged and it is significantly downgraded when germ cell function increases [28]. There exist mechanisms in germ cells which may induce somatic cell reprogramming and somatic stem cell pluripotency [29,30]. Kim et al [31] have shown that when male sticklebacks experience a benign and safe environment:…”
Section: Soma-to-germ Line Communicationmentioning
confidence: 99%